Effects of temperature and addition of zinc carboxylate to grease on the tribological properties of PA66 in contact with carbon steel. (January 2021) - Kunishima, T.; Nagai, S.; Kurokawa, T.; Galipaud, J.; Guillonneau, G.; Bouvard, G.; Abry, J.-Ch.; Minfray, C.; Fridrici, V.; Kapsa, Ph.
Abstract: In this study, the influence of temperature on the tribological properties of unreinforced or glass-fiber reinforced PA66 in contact with carbon steel under boundary lubrication with grease was studied when considering the temperature dependence of the mechanical properties on the sliding surface of PA66 and the tribochemical reaction to zinc carboxylate additives in grease. XPS and ToF-SIMS analyses revealed the formation of a carboxylate tribofilm on the steel surface and a zinc sulfide reactive film on the PA66 surface, which are related to the tribochemical reaction of the additives present in the grease applied. The formation of the tribofilm contributed to an improvement of the tribological properties, particularly at 80 °C. Graphical abstract: Image 1 Highlights: Influence of temperature on the tribological properties of PA66 in contact with steel under grease lubrication was studied. Temperature dependence on the PA66 mechanical properties and tribochemical reaction of grease additives was discussed. ToF-SIMS analyses revealed the formation of carboxylate tribofilm on the steel related to tribochemical reaction. XPS analyses revealed the formation of zinc sulfide reactive film on the PA66 related to tribochemical reaction. The formation of the tribofilm contributed to the improvement of the tribological properties, particularly at 80 °C.